Developing Outpatient Clinical Processes to Accelerate and Organize Patient Treatment Stages in Medical Clinics: An Evidence-Based Systematic Review Supporting Saudi Vision 2030 Healthcare Transformation - Alatiyyah, Maryam Taher; Alojayyan, Fatimah Zuhair; Abualruha, Fatimah Abbas Hassan; Alamer, Maryam Rajab; AlDawani, Alaa Ali; Alrushaid, Jawaher Ali; Aljassem , Noura Yaqoub; Alshahrani, Modhi Mohammed Sayaf; daghasi, Khadijah Hassan Mohammed; Alsaif, Samar Abdulaziz (Journal of Posthumanism, 2024)
Outpatient medical clinics play a critical role in ensuring timely, organized, and patient-centered treatment. However, fragmented workflows, inconsistent care transitions, and variable process structures continue to impede patient progress across treatment stages. This systematic review examines contemporary evidence on developing outpatient clinical processes that accelerate and organize patient treatment pathways, with specific emphasis on alignment with Saudi Arabia’s Vision 2030 Healthcare Transformation goals. Studies published between 2016 and 2024 were analyzed to evaluate models such as structured clinical sequencing, Lean-based workflow redesign, digital patient-flow monitoring, and integrated stage-transition protocols. Findings demonstrate that well-designed outpatient processes significantly reduce delays, improve care continuity, enhance interdepartmental coordination, and elevate overall patient experience. The review concludes that structured process development is essential for optimizing outpatient treatment stages and supporting Saudi Arabia’s national transformation efforts toward efficient, high-quality healthcare delivery.